PELATIHAN PEMBUATAN LAPORAN KEUANGAN PADA USAHA JUICE VANESHA DI AIR TIRIS KABUPATEN KAMPAR - Helmiati, Helmiati; Wahyu, Wadri; Tria Putri, Librina; Rahmawati, Rahmawati; Kasmawati, Kasmawati; Putri, Febriana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This activity started from the need for financial reports what traders need especially small traders. Lack of understanding, no training and perceptions regarding the preparation of financial statements complicated to make this activity carried out. Some problems, faced by partners can be overcome well when the activity is held. Method used the researcher is the lecture method and practical methods of preparing financial statements.Keywords: Traders, small traders, financial statement